An empiric analysis of the online market for the adventure travel tourism industry in Germany - Loureiro, S. M. C.; Sarmento, E. M.; Witt-Dörring, C. (Tourism and Hospitality International Journal, 2016)
The present article analyses the potential e-commerce in the tourism industry, particularly in the niche market of adventure travels. Tourists are increasingly booking travels using online platforms, especially Generation Y. This trend leads to the reduction the number of offline and traditional travel agencies and gives the opportunity to maximise the online travel market. E-commerce business is increasing as well as the market for adventure tourism. In this article we analyse existent online platforms for booking adventure travels and employ a survey to get the consumer perception about such platforms. The sample of 310 questionnaires analysed together with the nethnography conducted allow us to have useful information in order to better understand the phenomenon and give insights to managers and improve the service provided.